2007
DOI: 10.1007/s00442-007-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Allocating nitrogen away from a herbivore: a novel compensatory response to root herbivory

Abstract: Centaurea maculosa, an invasive North American plant species, shows a high degree of tolerance to the root-boring biocontrol herbivore, Agapeta zoegana. For example, infested individuals of C. maculosa often exhibit more rigorous growth and reproduction compared with their non-infested counterparts. Compensatory responses to aboveground herbivores often involve increases in leaf area and/or photosynthetic capacity, but considerably less is known about root system compensatory responses to belowground herbivory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 50 publications
2
62
2
Order By: Relevance
“…The rapid movement of resources belowground observed in our study is also in agreement with the growing body of literature demonstrating the transport of resources away from damaged sites and into roots and storage organs within hours following herbivory (Babst et al, , 2008Schwachtje et al, 2006;Newingham et al, 2007;Frost and Hunter, 2008;Kaplan et al, 2008;Gómez et al, 2010Gómez et al, , 2012. The adaptive value of sequestering resources to roots has been explained in various ways, including storing reserves for later regrowth to tolerate herbivory (Schwachtje et al, 2006).…”
Section: Newly Acquired 11 C Is Exported To Treated Young Leaves: Evisupporting
confidence: 91%
See 1 more Smart Citation
“…The rapid movement of resources belowground observed in our study is also in agreement with the growing body of literature demonstrating the transport of resources away from damaged sites and into roots and storage organs within hours following herbivory (Babst et al, , 2008Schwachtje et al, 2006;Newingham et al, 2007;Frost and Hunter, 2008;Kaplan et al, 2008;Gómez et al, 2010Gómez et al, , 2012. The adaptive value of sequestering resources to roots has been explained in various ways, including storing reserves for later regrowth to tolerate herbivory (Schwachtje et al, 2006).…”
Section: Newly Acquired 11 C Is Exported To Treated Young Leaves: Evisupporting
confidence: 91%
“…Previous studies using this short-lived isotope have narrowed their focus to short-term dynamics in resource allocation occurring immediately (within hours) following herbivory. These experiments suggest that plants respond to leaf damage by rapidly transporting recently fixed carbon from both damaged and undamaged tissues to roots, a response thought to be employed by plants to tolerate herbivory by bunkering resources away from sites of damage and into storage belowground for later regrowth (Babst et al, , 2008Schwachtje et al, 2006;Newingham et al, 2007;Frost and Hunter, 2008;Kaplan et al, 2008;Gómez et al, 2010Gómez et al, , 2012Orians et al, 2011).…”
mentioning
confidence: 99%
“…In addition, it was recently observed that, upon infection of spotted knapweed (Centaurea maculosa) with the root herbivore Agapeta zoegana, total nitrogen uptake was reduced and nitrogen was translocated from the root to the shoot of the plant (Newingham et al, 2007). These examples suggest that plants have evolved a way of limiting nutrient supply at the infection site.…”
Section: Organic Nitrogen Is Rerouted To Tumors From Systemic Source mentioning
confidence: 97%
“…If plants are attacked by root herbivores, assimilates can be remobilized above ground. The highly tolerant Centaurea maculosa responds to root herbivory by the knapweed moth by reducing its nitrogen (N) uptake but also shifting N to aboveground tissues (Newingham et al, 2007), suggesting that N allocation can be a determinant of tolerance. This idea is supported by the finding that after its leaves were clipped, the dwarf shrub Indigofera spinosa increased its root N uptake (Coughenour et al, 1990) and that Quercus serrata accumulates higher N levels in leaves (Takashima et al, 2004).…”
Section: Herbivore-induced Changes In Assimilation and Partitioning Omentioning
confidence: 99%